Discrimination, reversal, and shift learning in Huntington's disease: mechanisms of impaired response selection. - Lawrence, A; Sahakian, B; Rogers, R; Hodge, JR; Robbins, T (1999)
In a series of three experiments, we investigated different aspects of response selection in early-stage clinically symptomatic Huntington's disease (HD) patients in the context of discrimination learning. A series of structurally related response selection tasks involving discrimination, reversal, and shift learning were employed. In Experiment 1, the mechanisms of our previously reported [37] finding of impaired extra-dimensional shift learning were explored. The results suggested that impaired shift learning in HD is a result of perseverative responding. In Experiment 2, performance on a concurrent-pair (CP) discrimination and reversal task was examined. HD patients showed no deficits in CP discrimination learning or reversal. In Experiment 3, the performance of HD patients on a probabilistic discrimination and reversal task was examined. HD patients were impaired in the learning of a probabilistic discrimination, and also its reversal. This reversal deficit was again the result of perseverative responding. In addition, there was a strong correlation between HD patients' activities of daily living scores and reversal errors. The result are consistent with current theories of the role of the basal ganglia in cognition, and suggest specific impairments in response selection mechanisms in HD, in particular, in overcoming selection biases based on prior reinforcement.